The study of consumer behavior in the market of bakery products in the conditions of brand management - Maiboroda, Hanna; Майборода, Ганна Олександрівна; Майборода, Анна Александровна (My University, 2021)
Bread and bakery products are the traditional main component of the Ukrainian market basket. However, in recent years, there has been an annual reduction in the consumption of bakery products. According to the state statistics of Ukraine, the average annual consumption of bread products in 2015 was at the level of 103 kg per person, while in 2020 this figure was 98 kg per person. According to experts, one of the main reasons for the decline in this indicator is the decrease in consumer demand. Thus, the study of consumer behavior in the market of bakery products is a very relevant and indispensable issue. The object is the consumer behavior in the market of bakery products. The subject of research is a set of factors that determine consumer behavior in the market of bakery products. Methodology. To study consumer behavior, there was conducted a consumer survey at the oblast level using an external questionnaire with 15 questions to gather the necessary information. Since bread and bakery products are goods of daily and primary demand, the article determines that the general population is the entire population in the region. Their confidence probability is 95%, the confidence interval (error) is 5%, and the sample size was 500 respondents. The questionnaire was compiled using Google Forms software, and survey data were processed using Excel computer software. As a result of research, commodities were reduced, what actual to the consumer in this time, awareness about present brands, factors that induce the consumers of bakery products to render a preference to the separate brand. Nowadays, there is a need to supply the population with quality bakery products of a wide range, as well as those that take into account the consumer’s wishes. Manufacturers of bread and bakery products have every opportunity to meet these requirements, and the creation of a strong brand will help ensure the competitiveness of products. Research results may draw on the construction of the future general strategy of the enterprise. They will help in the construction of a strong brand of products for the achievement of competitive edges, an increase of market share, and the general profitability of enterprises.
Keywords: bakery products; consumer behavior; marketing; brand; brand management; enterprise strategy